Bacterial extracellular vesicles and their interplay with the immune system - Doré, Etienne; Boilard, Eric (Pharmacology & therapeutics (Oxford), 2023)
The mammalian intestinal tract harbors trillions of microorganisms confined within this space by mucosal barriers. Despite these barriers, bacterial components may still be found elsewhere in the body, even in healthy subjects. Bacteria can release small lipid-bound particles, also named bacterial extracellular vesicles (bEV). While bacteria themselves cannot normally penetrate the mucosal defense, bEVs may infiltrate the barrier and disseminate throughout the body. The extremely diverse cargo that bEVs can carry, depending on their parent species, strain, and growth conditions, grant them an equally broad potential to interact with host cells and influence immune functions. Herein, we review the current knowledge of processes underlying the uptake of bEVs by mammalian cells, and their effect on the immune system. Furthermore, we discuss how bEVs could be targeted and manipulated for diverse therapeutic purposes.